2014
DOI: 10.1118/1.4897388
|View full text |Cite
|
Sign up to set email alerts
|

Texture analysis on the fluence map to evaluate the degree of modulation for volumetric modulated arc therapy

Abstract: The contrast (d = 1) and variance (d = 1) calculated from fluence maps of VMAT plans showed considerable correlations with the plan deliverability, indicating their potential use as indicators for assessing the degree of modulation of VMAT plans. Both contrast and variance consistently showed better performance than the conventional modulation indices for VMAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(76 citation statements)
references
References 39 publications
4
72
0
Order By: Relevance
“…Park et al suggested a modulation index for VMAT (MIt) by quantifying variations in MLC speeds and accelerations weighted by variations in accelerations of gantry rotation and dose-rate simultaneously [14]. We also suggested textural features of the fluences generated by summations of all the delivered MUs with various shapes defined with MLCs at each control point (CP) as modulation indices for VMAT [17].…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Park et al suggested a modulation index for VMAT (MIt) by quantifying variations in MLC speeds and accelerations weighted by variations in accelerations of gantry rotation and dose-rate simultaneously [14]. We also suggested textural features of the fluences generated by summations of all the delivered MUs with various shapes defined with MLCs at each control point (CP) as modulation indices for VMAT [17].…”
Section: Introductionmentioning
confidence: 97%
“…Intensity modulated radiation therapy modulates photon beam intensities by modulating multi-leaf collimator (MLC) positions, while VMAT modulates photon intensities by modulating MLC positions, gantry rotation speed and dose-rate, simultaneously [1,4,7]. Although modulation of photon beam intensity is essential for both IMRT and VMAT, excessive modulation results in differences between calculated dose, which is the dose intended to be delivered to the patient, and the dose which is actually delivered to the patient [8][9][10][11][12][13][14][15][16][17][18][19]. Excessive modulation increases uncertainties in the mechanical operation of linac components, as well as increases the use of small or irregular MLC apertures of which dose calculation with commercial treatment planning system (TPS) is currently inaccurate as compared to that of large or regular MLC apertures [14,16,17].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…4,5) Moreover, calculations of the small or irregular fields which are frequently used for both IMRT and VMAT are not accurate even with the state-of-theart dose calculation algorithms. 7,8) Therefore, there is potential for both IMRT and VMAT to cause differences between the calculated dose distribution and the actually delivered dose distribution to a patient. 3) This can result in unintended treatment which is detrimental to patients, which should be avoided.…”
Section: Introductionmentioning
confidence: 99%